2012
DOI: 10.3109/15368378.2012.700293
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Microwave at X-Band in the aetiology of male infertility

Abstract: Reports of declining male fertility have renewed interest in assessing the role of environmental and occupational exposures to electromagnetic fields (EMFs) in the aetiology of human infertility. Testicular functions are particularly susceptible to electromagnetic fields. The aim of the present work was to investigate the effect of 10-GHz EMF on male albino rat's reproductive system and to investigate the possible causative factor for such effect of exposure. The study was carried out in two groups of 70-day o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
10
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 40 publications
3
10
0
1
Order By: Relevance
“…This range of frequency has been considered as hazardous for human health (Walani et al 2014). Increased usage of particularly 10 GHz microwave radiation is potentially strong to threat the human health, as also reported previously by our group (Kumar et al 2012;Sisodia et al 2013;Sharma et al 2014;Zhang et al 2014).…”
Section: Introductionsupporting
confidence: 79%
“…This range of frequency has been considered as hazardous for human health (Walani et al 2014). Increased usage of particularly 10 GHz microwave radiation is potentially strong to threat the human health, as also reported previously by our group (Kumar et al 2012;Sisodia et al 2013;Sharma et al 2014;Zhang et al 2014).…”
Section: Introductionsupporting
confidence: 79%
“…In contrast to these studies, Davis et al (22) showed that exposure to residential magnetic fields is not associated with increased risk of developing breast cancer. In addition to these, recent studies (2012) showed influences of (i) magnetic fields produced by incubators on the production of melatonin in newborns (23) ; (ii) electromagnetic field (EMF) exposures in the aetiology of male infertility (24) and 2.45-GHz wireless media on melatonin modulation in rats (25) .…”
Section: Introductionmentioning
confidence: 99%
“…The defense mechanism may be strengthened by the addition of exogenous substance. PDE treatment significantly lowered the radiation-induced LPO in terms of MDA 25 . Also reported increase in MDA in sperms of microwaves exposed male wistar rats.…”
Section: Discussionmentioning
confidence: 94%
“…These studies have generally used rodents. Experiments have pointed enhancement of the presence of free radicals after electromagnetic field exposure 4 . Excessive production of free radicals specifically reactive oxygen species (ROS), have also been reported in wide variety of clinical disorders and environmental stress 5 .…”
mentioning
confidence: 99%